Unlocking the Potential: Exploring the Impact of Online Assessment in English Language Teaching - Dewi Furwana; Fadhliyah Rahmah Muin; Andi A Zainuddin; Annisa Gita Mulyani (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
The primary aim of this research is to examine the types of online assessments utilized by English educators teaching tenth-grade students at SMAN 15 Luwu and to discern students' attitudes towards integrating online assessment methodologies. Employing a descriptive qualitative approach, data collection involved the administration of questionnaires and conducting interviews. Interviews were conducted with both English instructors and students from SMAN 15 Luwu. Findings reveal that English instructors at SMAN 15 Luwu employ online assessment tools such as Google Forms, Google Classroom, Quizzes, and Instagram. These tools present various advantages, disadvantages, and challenges, including the complexities of designing appropriate assessments, managing student behavior, and grappling with unreliable internet connectivity. Concurrently, student perspectives toward online assessment exhibit both favourable and unfavourable inclinations. Positive perceptions include enjoyment of the online assessment, prompt feedback acquisition, flexibility, time efficiency, effectiveness, and increased confidence in online assessment execution.